New species of genus Atractides Koch, 1837 (Acari: Hydrachnidiae, Hygrobatidae) from Qinghai, China - Zhang, Yu-Hao; Li, Hai-Tao; Li, Cai-Yun; Guo, Jian-Jun (European Journal of Taxonomy, 2022)
The paper deals with five new species of the genus Atractides Koch, 1837 (Acari: Hydrachnidiae, Hygrobatidae) collected from Qinghai Province, P.R. China, Atractides (Atractides) biprojectus Zhang, Li & Guo sp. nov., Atractides (Atractides) smiti Zhang, Li & Guo sp. nov., Atractides (Atractides) menyuanensis Zhang, Li & Guo sp. nov., Atractides (Atractides) longiprojectus Zhang, Li & Guo sp. nov. and Atractides (Atractides) xianmiensis Zhang, Li & Guo sp. nov. All the new species are described and illustrated in detail, and all the type specimens are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).